The coin as a discourse: an analysis of the representations of Octavian, Cleopatra and Mark Anotny (De Rebus Antiquis, 2020)
The present article discusses about the representation of Octavius, Mark Antony and Cleopatra in three coins, to reflect about how the ancient mintage contributed for these personages could shape their images to the populus romanus in general.
Keywords: Coins; Representation; Roman Republic